MODEL OF THE RHETORICAL COMPETENCE FORMATION OF FUTURE UNIVERSITY TEACHERS - Lyubov Kanibolotska (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article is devoted to the formation of the rhetorical competence of future teachers, including grounding and development model of competence specified in the professional training for professional activity at universities. It is proved that the model of rhetorical competence involves the unity of methodological, technological, diagnostic and remedial teaching units through compliance with pedagogical conditions whichenhance the development of skills and abilities of teachers to rhetorical activity. It has been set that the goal realization is carried out due to certain methodological approaches and three successive stages; compliance with the set principles, methods and forms provides sufficient and high levels of rhetorical competence of future university teachers.